Analisis Pelaksanaan Penilaian Motorik Halus Anak dengan Portofolio di TK Asiah - Hermawati, Hermawati (ACIECE, 2019)
Assessment is very related to education, because in learning assessment perusos much needed schools and teachers, while the purpose of this assessment is to find out on the achievement of child development, many types of assessments that can be used by teachers, one of which is portfolio, how the assessment process is carried out teachers through portfolio, whether the portfolio is suitable to be used to determine the development of fine motor children, the purpose of this study is to look at the process, and stages of assessment of fine motor children through a portfolio at Kindergarten Asiah. This research was conducted by observation, interviews with the parties concerned, with the teacher, portfolio assessment by collecting the work made by children from the beginning of learning to the end, the researchers analyzed the portfolio assessment process at Kindergarten Asiah, researchers found that the activities of fine motor assessment of children with a portfolio has been carried out in accordance with the provisions, starting from the planning, implementation, and assessment stages, such as giving a star on each child's work, the teacher arranges a portfolio ranging from peper, content, restrictions, and explanations of child development, and displays the best children's work and other works are used as portfolio forms of archival portfolio stofmap